Computational study of sloshing in spherical tanks and the effect of using annular baffle over slosh force frequency and damping. (7th January 2022) - Ahmad, Habib; Ahmed, Ammar; Baila, Ismail; Shah, Ajmal; Iqbal, Mazhar
Partially filled liquid containers are subjected to sloshing when acted upon by an external force or acceleration. The sloshing liquid applies varying forces on walls of the container that have to be included in its design. In this study, the CFD method was validated against experimental data from existing literature. Using the validated method, the impact of the liquid fill level in the container, initial perturbation velocity, and variation in time step size over the frequency and damping of sloshing force was studied. Moreover, a novel idea of introducing an annular baffle in spherical tanks has been proposed to minimise the effects of sloshing on the container. The damping effect of the annular baffle in a spherical container was analysed using a validated CFD method. The result comparison of the two cases shows a significant increase in the damping of slosh force by the introduction of an annular baffle.